Evaluation of a Tangential Map-Based Nomogram for Intrastromal Corneal Ring Segments' Implantation in Keratoconus: One Year Results. (19th February 2020) - Zaky, Adel Galal; KhalafAllah, Mahmoud Tawfik; Sarhan, Abdelrahman Elsebaey; Elsawy, Moataz Faiz
Abstract : Purpose . To evaluate a new tangential map-based nomogram versus the axial map-based nomogram for ICRS in keratoconus. Methods . A prospective case series study including 64 eyes of 64 patients who underwent ICRS implantation. Cone location was determined for each eye with two maps: the axial and the tangential. Appropriate ring selection was determined using two surgical nomograms: axial map-based and tangential map-based. Visual, refractive, and topographic outcomes were assessed before, as well as at 3, 6, and 12 months after ICRS implantation. Results . The cone location, and consequently the ring selection, was significantly different in the two nomograms with a "centralization tendency" in the tangential map. In the axial group, UDVA and CDVA improved from 0.12 ± 0.04 and 0.24 ± 0.08 to 0.28 ± 0.08 and 0.4 ± 0.1, respectively. Similarly, MRSE substantially decreased from −6.7 ± 3.3 to −1.2 ± 1.1 D at 12 months after the procedure. In the tangential group, UDVA and CDVA improved from 0.09 ± 0.06 and 0.2 ± 0.1 to 0.5 ± 0.2 and 0.7 ± 0.2, respectively. MRSE substantially decreased from −4.9 ± 1 D to −1.00 ± 1.6 D at 12 months after the procedure. The UDVA gain was significantly higher in the tangential group: 0.35 compared to 0.15 at 12 months, P = 0.01 ∗ . Similarly, the gain in the CDVA was 0.4 and 0.15 in the tangential and axial groups, respectively, at 12 months, P = 0.003 ∗ . At 12 months, the tangential map showed superiority in UDVA, CDVA, and MRSE in the peripheral cone location, but not the central and paracentral ones. Conclusion . The tangential map-based nomogram attained better visual and refractive outcomes at 1 year. In addition, the cone location was significantly different between both maps with a centralization tendency in the tangential one.